Predicting the outcomes of NCAA basketball championship games - Stekler, H. O.; Klein, A. (Journal of Quantitative Analysis in Sports, 2012)
This paper uses the difference in seeding ranks to predict the outcome of March Madness games. It updates the Boulier-Stekler method by predicting the outcomes by rounds. We also use the consensus rankings obtained from individuals, systems and poll. We conclude that the consensus rankings were slightly better predictors in the early rounds but had the same limitations as the seedings in the later rounds.